Influence of Cooking by Boiling on Lead and Cadmium in Meat and Liver of Chickens - E Hashem, Wasan; A Abdaljaleel, Raghad (The Iraqi Journal of Veterinary Medicine, 2024)
Heavy meals are widely known as environmental pollutants due to their toxicity, heat stability, long staying in the atmosphere, and their capability to accumulate in the body. The current experiment investigates the concentration of lead (Pb) and cadmium (Cd), which are considered heavy metals in the liver and meat of fresh and imported frozen chicken, by studying the effect of cooking process using the boiling method. A total of 80 samples were randomly collected and examined: 40 frozen (10 from each of the liver and meat) before and after cooking) and 40 fresh (10 from each the liver and meat) before and after cooking) from different regions in AL-Karkh Province, Baghdad. Atomic Absorption Spectrometry device was used to evaluate the concentration of Pb and Cd. The results revealed that, in the concentration of Pb in the frozen cooked liver was significantly higher 321.8 ppm in comparison to fresh uncooked liver was 84.20 ppm. In contrast, meat samples indicated that neither cooking nor storage significantly affected the concentrations of Pb. The results also indicated that Cd concentration in meat tissue was significantly higher in fresh cooked (133.7 ppm) compared to frozen cooked (24.30 ppm). For correlation, a non-significant correlation between Pb and Cd concentration at the 0.05 level in liver and meat before and after cooking was recorded. The present study concluded that cooking by boiling method which is a traditional method that is used in Iraqi kitchens, can cause an increase in Pb, and Cd concentration. High concentrations of Pb or Cd in meat and liver may come from the environment, food consumed by chickens, cooking procedures, pans used, and sources of water may affect metal concentrations‎‎‎.